Metabolite profiling with HPLC-ICP-MS as a tool for in vivo characterization of imaging probes - Eszter Boros; Omar R. Pinkhasov; Peter Caravan (SpringerOpen, 2018)
Abstract Background Current analytical methods for characterizing pharmacokinetic and metabolic properties of positron emission tomography (PET) and single photon emission computed tomography (SPECT) probes are limited. Alternative methods to study tracer metabolism are needed. The study objective was to assess the potential of high performance liquid chromatography - inductively coupled plasma - mass spectrometry (HPLC-ICP-MS) for quantification of molecular probe metabolism and pharmacokinetics using stable isotopes. Methods Two known peptide-DOTA conjugates were chelated with natGa and natIn. Limit of detection of HPLC-ICP-MS for 69Ga and 115In was determined. Rats were administered 50-150 nmol of Ga- and/or In-labeled probes, blood was serially sampled, and plasma analyzed by HPLC-ICP-MS using both reverse phase and size exclusion chromatography. Results The limits of detection were 0.16 pmol for 115In and 0.53 pmol for 69Ga. Metabolites as low as 0.001 %ID/g could be detected and transchelation products identified. Simultaneous administration of Ga- and In-labeled probes allowed the determination of pharmacokinetics and metabolism of both probes in a single animal. Conclusions HPLC-ICP-MS is a robust, sensitive and radiation-free technique to characterize the pharmacokinetics and metabolism of imaging probes.